A demonstration of higher‐order response class development in children. Issue 3 (26th April 2018) - Dixon, Mark R.; McCord, Brandon E.; Belisle, Jordan
Abstract : We evaluated a procedure for teaching two children, one typically developing and one with autism, a higher‐order generalized operant response class of unscrambling sight words. The procedures were efficacious in teaching the participants to unscramble words appearing in isolation and in the context of a sentence, with 98% of the presented discriminative stimuli novel to the participants.